2006
DOI: 10.1176/ajp.2006.163.12.2064
|View full text |Cite
|
Sign up to set email alerts
|

Atypical Antipsychotics in the Treatment of Schizophrenia During Pregnancy and the Postpartum

Abstract: In this report, we discuss the case of a woman with paranoid schizophrenia who hoped to become pregnant. She was taking a stable daily dose of antipsychotic medication when she initially sought consultation about the safety of medication during pregnancy. This case examines 1) the challenges that arise when women with psychiatric disorders require treatment during pregnancy and lactation and 2) the balancing of competing needs that form the backbone of the risk-benefit analysis of medication use during pregnan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 39 publications
0
34
0
Order By: Relevance
“…34 Two neonates in the prospective cases had seizures, and one premature child had multiple anomalies and delayed development. There were five congenital malformations and five unspecified perinatal complications in the retrospective case reports.…”
Section: Clozapinementioning
confidence: 94%
See 4 more Smart Citations
“…34 Two neonates in the prospective cases had seizures, and one premature child had multiple anomalies and delayed development. There were five congenital malformations and five unspecified perinatal complications in the retrospective case reports.…”
Section: Clozapinementioning
confidence: 94%
“…Although there were three reports of limb malformations with the use of haloperidol and one with penfluridol in the first trimester, these effects were not replicated in other studies. 34 Another study found an increased risk of premature birth and lower birth weight in infants exposed to haloperidol and penfluridol. 35 Use of FGAs is limited by the risk of extrapyramidal symptoms (EPS) in the mother and possibly the neonate.…”
Section: First-generation Antipsychoticsmentioning
confidence: 99%
See 3 more Smart Citations